Updates from Gastrointestinal ASCO 2015 - Shaheenah Dawood (Indian Journal of Medical and Paediatric Oncology)
This year at ASCO GI we saw important data presented that has continued to shape the way we treat GI malignancies. Several important questions were addressed. Can we avoid surgery among patients with rectal tumors? Data from a provocative retrospective study indicated that certain subgroups of patients might not need surgery thereby preserving the rectum without compromising survival outcome. What is the role of ramicurumab among patients with advanced colorectal cancers? Data from the phase III RAISE trial revealed that the addition of ramicurumab to second line therapy significantly improved median overall survival. What is the role of immunotherapy in GI malignancies? Interesting results from the KEYNOTE-012 trial was presented that looked at the efficacy of pembriluzumab among patients with advanced gastric cancer with the investigators reporting interesting results of an objective response rate of 22.1% and a 6 months progression free survival of 24%. In this review we will briefly present these and other important highlights of the ASCO GI meeting.